EVALUATION OF THE RESULTS OF EXAMINATION OF NEWBORNS WITH INTRAUTERINE INFECTION - Sirojiddinova Khiromon Nuriddinovna (Web of Journals Publishing, 2024)
Intrauterine infections are caused mainly by bacterial and viral pathogens that have penetrated to the fetus from the mother before or during childbirth. Intrauterine infection (IUI) has numerous manifestations, such as conjunctivitis, rhinitis, pyoderma, pneumonia, hepatitis, otitis, meningoencephalitis, up to the development of sepsis. However, intrauterine infection does not always lead to generalized IUI, in some cases infected children do not have any clinical symptoms of the disease. The aim of the study was to study the most common variants of IUI in newborns and to determine their relationship with infectious urogenital and extragenital diseases of the mother. The analysis of the birth histories and the development histories of newborns, including the somatic and obstetric-gynecological anamnesis of the pregnant woman, the course of pregnancy and childbirth, the results of clinical and laboratory studies, as well as the assessment of the child's condition after childbirth, was carried out.
Keywords: intrauterine infections, newborns, extragenital diseases